Imaging Characteristics of Recurrent Pleomorphic Adenoma of the Parotid Gland - Moonis, G.; Patel, P.; Koshkareva, Y.; Newman, J.; Loevner, L.A. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Pleomorphic adenoma is the most common parotid neoplasm. It has a relatively high rate of recurrence after surgery. Imaging features of recurrent parotid pleomorphic adenoma have been infrequently reported in the radiology literature. In the present study, we reviewed our institutional experience with imaging of recurrent parotid pleomorphic adenomas.MATERIALS AND METHODS: Retrospective imaging and chart review of 24 patients (9 men, 15 women; age, 29–63 years) with recurrent pleomorphic adenoma of the parotid were performed. Images were reviewed as to the margins, site, multiplicity, signal intensity, and enhancement pattern of the recurrent lesions by 2 neuroradiologists.RESULTS: We found a high incidence of multiple lesions in the operative bed, most of which were extremely bright on T2-weighted images; some of the lesions demonstrated a cystic appearance with peripheral enhancement. We also noted tiny lesions in the subcutaneous fat and in regions distant from the immediate operative bed.CONCLUSION: Although recurrent disease is usually clinically apparent, sometimes prior surgical history is lacking or recurrence may be detected on routine surveillance imaging after initial surgery. The presence of solitary or multiple subcutaneous T2 hyperintense lesions in the operative bed, subcutaneous fat, and/or spaces adjacent to the parotid in patients with prior parotidectomy for pleomorphic adenoma is consistent with the diagnosis of neoplastic recurrence. The radiologist should maintain a high index of suspicion for recurrent pleomorphic adenoma with this characteristic imaging appearance.